Working hours and health - key research topics in the past and future - Mikko Härmä; Göran Kecklund; Philip Tucker (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVE: This paper discusses the past and present highlights of working hours and health research and identifies key research needs for the future. METHOD: We analyzed over 220 original articles and reviews on working hours and health in the Scandinavian Journal of Work, Environment & Health published during the last 50 years. Key publications from other journals were also included. RESULTS: The majority of identified articles focussed on the effects of shift and night work, with fewer studying long and reduced working hours and work time control. We observed a transition from small-scale experimental and intensive field studies to large-scale epidemiological studies utilizing precise exposure assessment, reflecting the recent emergence of register-based datasets and the development of analytic methods and alternative study designs for randomized controlled designs. The cumulative findings provide convincing evidence that shift work and long working hours, which are often associated with night work and insufficient recovery, increase the risk of poor sleep and fatigue, sickness absence, occupational injuries, and several chronic health conditions such as cardiovascular diseases and cancer. The observed risks are strongly modified by individual and work-related factors. CONCLUSIONS: Although the observed health risks of shift work and long working hours are mostly low or moderate, the widespread prevalence of exposure and the hazardousness of the many associated potential outcomes makes such working time arrangements major occupational health risks. Further research is needed to identify exposure-response associations, especially in relation to the chronic health effects, and to elucidate underlying pathways and effective personalized intervention strategies.